Kajian Indeks Kepuasan Masyarakat terhadap Pelayanan Rumah Sakit Umum Daerah Pambalah Batung Amuntai - Latifa Suhada Nisa; Maliani Maliani; Siska Fitriyanti; Dewi Siska (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2020)
Based on Law Number 25 Year 2009 regarding Public Services, every public service provider is demanded to always improve the quality of its services. One effort to meet the need to improve service quality is to carry out a Community Satisfaction Survey (SKM), where the implementation has been regulated in Permenpan No. 14 of 2017. SKM in this study was conducted at the Regional General Hospital (RSUD) Pambalah Batung Amuntai, Hulu Sungai Utara Regency (HSU). SKM is conducted to be able to measure and analyze the Community Satisfaction Index. Descriptive methods with qualitative and quantitative approaches (mix method) were used in this research. The results of data analysis showed that the IKM of Pambalah Batung Amuntai Hospital was 78.24, which is rated as